1998
DOI: 10.1161/01.str.29.1.98
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Hematocrit Decreases With Hemodynamic Compromise in Carotid Artery Occlusion

Abstract: Background and Purpose-This study investigated whether in patients with internal carotid artery occlusion the regional cerebral hematocrit correlates with cerebral hemodynamics or metabolic state and, if so, how the regional cerebral hematocrit changes in the hemodynamically compromised region. Methods-We used positron emission tomography to study seven patients with unilateral internal carotid artery occlusion and no cortical infarction in the chronic stage. The distributions of red blood cell and plasma volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 31 publications
2
28
0
Order By: Relevance
“…This significant reduction of parameters in the region of cerebral infarction was similar to a previous report (Temma et al, 2006). A single-compartment analysis used in the steady-state method may overestimate cerebral water clearance and tissue counts (Ohta et al, 1992(Ohta et al, , 1996; however, this method was established in human PET studies and many studies with CVD patients were reported (Yamauchi et al, 1996(Yamauchi et al, , 1998(Yamauchi et al, , 1999Okazawa et al, 2001;Ouchi et al, 2001). Although slightly different values were observed between the steady-state method and the bolus administration method in a previous study with CVD, the values were not significantly different (Okazawa et al, 2001).…”
Section: Discussionsupporting
confidence: 87%
“…This significant reduction of parameters in the region of cerebral infarction was similar to a previous report (Temma et al, 2006). A single-compartment analysis used in the steady-state method may overestimate cerebral water clearance and tissue counts (Ohta et al, 1992(Ohta et al, , 1996; however, this method was established in human PET studies and many studies with CVD patients were reported (Yamauchi et al, 1996(Yamauchi et al, , 1998(Yamauchi et al, , 1999Okazawa et al, 2001;Ouchi et al, 2001). Although slightly different values were observed between the steady-state method and the bolus administration method in a previous study with CVD, the values were not significantly different (Okazawa et al, 2001).…”
Section: Discussionsupporting
confidence: 87%
“…Under the pathologic conditions of brain ischemia, the error may cause underestimation of OEF in the ischemic brain tissue because hematocrit in the local small vessel would decrease to some extent. 30 Another potential error comes from paramagnetic sources other than deoxyhemoglobin, which can induce an additional signal-intensity loss in MR images. Therefore, the presence of hemosiderin may lead to an unavoidable error in the measurement of OEF in the local brain.…”
Section: Discussionmentioning
confidence: 99%
“…Regional cerebral hematocrit may change with pathologic condition. For example, in patients with occlusive cerebrovascular disease, regional decreases in cerebral hematocrit, which may be associated with greater decreases in plasma velocity than in RBC velocity, has been reported (Yamauchi et al, 1998(Yamauchi et al, , 1999. In PET studies, the assumption of constant hematocrit ratio will cause underestimation of CBV and MTT in such brain regions.…”
Section: Effect Of Hematocritmentioning
confidence: 99%